An Analysis of Some Labor Market Regulation Segments of Slovakia in Reflection to the Hungarian Labor Market Development Measures Going into Effect in 2025 - Csaba Lentner; Zsolt Horbulák (Institutiones Administrationis)
Under the active Hungarian public finance model, in place since 2010, labor market regulation has come under strong state influence and control. As its keys result, an additional one million people are now on the labor market, the employment rate has risen from 52% to almost 80%, while the unemployment rate remained below 4%, even during the 2020–2024 crisis years. The Hungarian government provides targeted labor market subsidies, and starting in 2025, has introduced new rules to strengthen the labor market. These government actions are designed to prevent westward migration and to help both the families and society as a whole to prosper. Following a brief overview of these Hungarian actions, the study places its findings next to those on Slovakia, a neighboring country at a similar level of development. As such, it presents a detailed analysis of the key elements of the Slovakian labor market regulations with a view to highlighting its differences in the regulatory methodologies of the two countries.